Assesment Of The Effectiveness To Which Lecturers Apply Learner-Centered Techniques In Teaching And Learning Process In Universities In Tanzania: A Case Study Of Mwenge Catholic University (International Journal of Scientific Research and Management (IJSRM), 2018)
The study examines the effectiveness of implementing Learner Centered Techniques and approaches among lecturers at Mwenge Catholic University. Learner Centered Technique (LCT) is a competence-based instructional approach which seeks teachers’ active involvement of students in the classroom processes with emphasis on students’ learning. The study was guided by the following research questions; To what extent do lecturers and teacher students familiar with Learner Centered Teaching at MWECAU? Which LCTs are most preferred by most lecturers during teaching and learning at MWECAU? What skills does the LCT promote in teaching and learning process? What measures can be put in place to improve the implementation of LCT at MWECAU? Both qualitative and quantitative designs were used to examine to what extent lecturers at MWECAU apply LCT targeting lecturers and students at MWECAU. Questionnaires were the main tool used to collect data and statistical package for social sciences (SPSS) version 20 was used to analyze quantitative data. Findings revealed that to a higher extent the lecturers in the university understudy use learner centered techniques in teaching and assessment. The findings also indicate that Learner Centered Techniques promotes students’ creativity, critical thinking and independent learning. The Learner Centered Techniques used to encourage students’ engagement and in problem-solving skills to apply in daily life.